2021
DOI: 10.1021/acsaem.1c00876
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bimetallic Pd–X (X = Ni, Co) Nanoparticles Assembled on N-Doped Reduced Graphene Oxide as an Anode Catalyst for Highly Efficient Direct Sodium Borohydride–Hydrogen Peroxide Fuel Cells

Abstract: Bimetallic Pd−X (X = Ni, Co) nanoparticles on nitrogen-doped reduced graphene oxide (N-rGO) are fabricated through a thermal solid-state technique followed by polyol reduction to be used as anode electrocatalysts for direct sodium borohydride−hydrogen peroxide fuel cells. The physical characterization of synthesized materials is investigated using Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…00-04-0850), it is concluded that all the peaks for synthesized catalysts are placed between the peaks of Pd and Ni metal NPs. These results reveal the successful preparation of the Pd-Ni/NrGO nanostructure in good accordance with those reported in the literature [39,[47][48][49][50].…”
Section: Physical Characterization Of Nanocatalystssupporting
confidence: 91%
See 4 more Smart Citations
“…00-04-0850), it is concluded that all the peaks for synthesized catalysts are placed between the peaks of Pd and Ni metal NPs. These results reveal the successful preparation of the Pd-Ni/NrGO nanostructure in good accordance with those reported in the literature [39,[47][48][49][50].…”
Section: Physical Characterization Of Nanocatalystssupporting
confidence: 91%
“…Moreover, a new peak appears at 1187 cm −1 which can be related to the C-N bonds. These observations provide valuable information in regard to the existence of nitrogen-containing groups in the synthesized catalyst support in close agreement with reports in the literature [39][40][41]. Figure 1b presents XRD patterns of GO, NrGO, and Pd-Ni/NrGO samples; the existence of sharp peaks in these XRD patterns characterize a crystalline structure for the synthesized materials.…”
Section: Physical Characterization Of Nanocatalystssupporting
confidence: 89%
See 3 more Smart Citations